Custom formed orthoses in cycling - O`Neill, B. C.; Graham, K.; Moresi, M.; Perry, P.; Kuah, D (Journal of Science and Medicine in Sport, 2011)
To assess the effects of currently used prescribed in-shoe custom foot orthoses (CFOs) on a number of biomechanical variables during the power phase of cycling, including: hip adduction, knee abduction and tibial internal rotation. Before and after cross-over study recording subjects` biomechanical variables with and without their CFOs. Twelve competitive cyclists, currently using prescribed in-shoe CFOs, performed two exercise bouts on a stationary trainer, with 3-dimensional data recorded on an 8 camera Vicon Mx system. 2-way ANOVA statistical analysis of Null vs Orthotic condition, and left leg vs right leg. No systematic effects from the CFOs were seen. A trend towards reduced tibial internal rotation range of movement was found (P<0.072). Significant subject-specific effects from the CFOs were seen (P<0.05). Three distinct patterns of knee movement were observed. All subjects had significant left to right leg differences. CFOs do not produce systematic effects on cycling biomechanics. Significant subject-specific biomechanical effects can be produced by CFOs utilizing rearfoot and/or forefoot wedges. An individualised approach to orthotic prescription, and attention to the forefoot-rearfoot relationship, is recommended.